2019
DOI: 10.11648/j.ajce.20190704.11
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Fly Ash and Bagasse Ash Using as a Sub-Grade Material

Abstract: Expansive soil is prone to large volume changes (swelling and shrinking) that are directly related to changes in moisture. So the low bearing strength and high compressibility behavior of soil can cause severe damage to subgrade. In this research the enumeration of the strength of soil by adding different types of ground improvement materials like as fly ash and bagasse ash in order to overcome such type of damages. The California Bearing Ratio (CBR) test to determine the stability of subgrade soil by adding f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…With the addition of 7% cement the CBR increased to 175.7% and thereafter decreased to 102.6% at 9%. The increase in values of CBR is consistent with the findings of [39][40][41]. The increase in the values of CBR upon the addition of cement may be attributed to the presence of adequate amounts of calcium required for the formation of Calcium Silicate Hydrate (CSH) and Calcium Aluminate Hydrate (CAH), which are the major compounds responsible for strength gain [42].…”
Section: A Mechanical Properties 1) Omc Mdd Cbr and Ucs For Cement-st...supporting
confidence: 85%
“…With the addition of 7% cement the CBR increased to 175.7% and thereafter decreased to 102.6% at 9%. The increase in values of CBR is consistent with the findings of [39][40][41]. The increase in the values of CBR upon the addition of cement may be attributed to the presence of adequate amounts of calcium required for the formation of Calcium Silicate Hydrate (CSH) and Calcium Aluminate Hydrate (CAH), which are the major compounds responsible for strength gain [42].…”
Section: A Mechanical Properties 1) Omc Mdd Cbr and Ucs For Cement-st...supporting
confidence: 85%
“…The addition of 8% CCR and 9% BA, provided the highest compressive strength of the stabilised RE material. Rashid et al (2019) carried out California bearing ratio (CBR) study to determine the stability of soil. It was found that FA would perform better than BA for soil stabilisation.…”
Section: Introductionmentioning
confidence: 99%